Risk of field cultivation of pickling cucumber caused by unfavorable sunshine duration conditions (Scientia Agricola, 2011)
Solar energy, accessible to plants during sunshine from the sunrise to the sunset is of key importance in productivity of agrocenoses. The aim of the work was to determine risk of pickling cucumber cultivation caused by an unfavorable course of sunshine duration in Poland on the basis of a 40-year research period 1966-2005. The research into the subject was undertaken due to frequent occurrence of sunshine deficiency in Poland and its high temporal and spatial variability. Effect of solar conditions described by sunshine duration in the five development stages on the quantity of the total and marketable yield of cucumber with consideration of a linear trend of an independent variable was determined by means of multiple regression analysis. The accuracy of the equations was evaluated on the basis of, among other things, determination coefficient, average relative forecast error and the indexes: mean bias error (MBE), mean absolute bias error (MABE) and root mean square error (RMSE). Cucumber (Cucumis sativus L.) yield was confirmed for the period from the end of emergence to the beginning of flowering and from the beginning of harvesting to the end of harvesting. Cucumber yield was lower by 18% than the multiannual average in the years 1966-2005 every 1.5-2 years -in the case of the occurrence of the shortage in the period from the end of emergence to the beginning of flowering and by 12-15% every 2-3 years in the period from the beginning of harvesting to the end of harvesting. In four years, out of the 40 considered ones, simultaneously in both cucumber development stages, unfavorable solar conditions occurred, causing reduction by at least 5% in the total yield of the plant in Poland, and in three years - the marketable yield.